Dampak ekonomi dari event olahraga Walikota Solo cup 2022 - Wijanarko, Bambang; Iqbal Doewes, Rumi; Nuryadin, Islahuzzaman; Kunta Purnama, Sapta; Ismaryati, Ismaryati (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Organizing sports events have played a role in the local community's economy. The research purpose was to estimate how the implementation of the 2022 Solo Mayor Cup sporting event will play a role in the local community's economy, such as output, added value, income creation, and job creation. The study used a quantitative descriptive study with a survey design. A total of 1,470 visitor surveys were generated (426 local visitors and 1,044 non-local visitors). The study used a quantitative descriptive study with a survey design. A total of 1,470 visitor surveys were generated (426 local visitors and 1,044 non-local visitors). The results show that the 2022 Solo Mayor Cup sporting event created an average output of 1,109.15 thousand rupiahs, an average income of 124.40 thousand rupiahs, and an average gross value added of 262.40 thousand rupiahs, and an average workforce can be absorbed 207 people. The existence of the 2022 Solo Mayor Cup sporting event can increase the host economy due to relevant direct expenditures from sports bodies for wages and due to visitors spending on accommodation, transportation, food and beverages, and shopping. Apart from that, the 2022 Solo Mayor Cup sporting event also created new job opportunities, increasing household income. The Walikota Solo Cup 2022 has a positive economic impact on the people of Solo.